EVALUASI PENGEMBANGAN POTENSI “ANCIENT TRACK ONE” DENGAN MODEL CIPP DI DESA WISATA BEDULU DAN DESA BURUAN KABUPATEN GIANYAR - Sastrawan, I Gede Anom; Paturusi, Syamsul Alam; Arida, Nyoman Sukma (Jurnal Master Pariwisata (JUMPA), 2017)
The study aims to evaluate the quality improvement activities in order to appeal tracking tours in Gianyar regency, Bali. The concept used in this study is the evaluation of the concept, the concept of tourism potential and attractions as well as the concept of rural tourism, village tourism concept, the concept of alternative tourism, archaeological tourism concept and the concept of alternative tourism. The theory is used to analyze this study is the evaluation theory, the theory of sustainable tourism development and tourism destination development theory are analyzed with models CIPP (Context, Input, Process, Product). Moreover, the constraints faced in the implementation of development Ancient Tracking One at the Tourism Village Bedulu and Villages Buruan. Associated with the constraints in the development of Ancient Track One can be seen from has not been established as a legal organization as a manager of a tourist attraction. Suggestions put forward in this study, namely: commitment required for the implementation of tourism activities Ancient Track One, with no synchronization between the aspects of context, input, process and product development of tourism in Ancient Track One, as a tourist attraction based on historical and archaeological heritage, tourist areas need to be set right brand that can distinguish between this region with other regions.